AGENSI PEREMPUAN DALAM PRAKTEK PERNIKAHAN DINI DI DESA DAWUHAN GRUJUGAN BONDOWOSO (Kafa`ah: Journal of Gender Studies, 2022)
The differences of marriage standarization between parents and children, is one of the reasons for the child's rejection of the wishes of his parents. Often times the rejection that occurs in children against the wishes of their parents is the result of a mismatch between the wishes of their parents and the wishes of a child, therefore, the author wants to examine how and what forms of rejection of children against the wishes of their parents who want to marry them immediately and what impact it will have. to harmony in the family. This article using Anthony Giddens' agency theory, for Giddens actors and structures cannot be separated, but are interrelated between actors and structure. According to Giddens, the relationship is a duality (reciprocity), not a relationship of dualism (opposition). Search data in this study is using field observations and direct interviews with informants. In the study, it was found that the form of rejection of a child against the wishes of parents who want to get married immediately turned out to be quite diverse, ranging from the desire to find work as an excuse to avoid communication with parents, for example away from home such as looking for work, who are still students, have reasons to stay at the pesantren, until the reason for their desire to continue their studies, are some of their efforts to avoid pressure from their parents to marry them off. The rejection by a child against the wishes of parents, in fact also has an impact on harmony in the family itself, how there are differences in desires between children and parents and the choice of children who choose to build distance with their parents, is a measure of the cause of the lack of harmony. relationships in the family.